Archaeal Diversity of Upland Rice Field Soils Assessed by the Terminal Restriction Fragment Length Polymorphism Method Combined with Real Time Quantitative-PCR and a Clone Library Analysis - Nishizawa, Tomoyasu; Komatsuzaki, Masakazu; Kaneko, Nobuhiro; Ohta, Hiroyuki (Microbes and environments, 2008)
The PCR amplification-based analysis of microbial diversity is subject to potential problems. In this study, to minimize the bias toward a 1:1 ratio in multitemplate PCR, a real-time PCR assay was carried out using a quenching fluorescence dye primer and amplification efficiency was monitored. Then terminal-restriction fragment length polymorphism (T-RFLP) profiling was performed using the PCR product with minimized PCR bias. This method was applied to an analysis of the diversity of the archaeal community in an upland rice field under different tillage systems and winter cover cropping. Terminal restriction fragments (T-RFs) of PCR-amplified archaeal 16S rRNA genes were assigned to the gene sequences recovered from the same soil by using an archaeal 16S rRNA gene clone library. Our results indicated that soil archaeal members were not influenced but the relative abundance of archaeal species particularly those belonging to Crenarchaeota which changed between the tillage and non-tillage treatments.